Emerging clinical experience with vaccines against group B meningococcal disease - Wilkins, A; Snape, M (Elsevier, 2017)
The prevention of paediatric bacterial meningitis and septicaemia has recently entered a new era with the availability of two vaccines against capsular group B meningococcus (MenB). Both of these vaccines are based on sub-capsular proteins of the meningococcus, an approach that overcomes the challenges set by the poorly immunogenic MenB polysaccharide capsule but adds complexity to predicting and measuring the impact of their use. This review describes the development and use of MenB vaccines to date, from the use of outer membrane vesicle (OMV) vaccines in MenB outbreaks around the world, to emerging evidence on the effectiveness of the newly available vaccines. While recent data from the United Kingdom supports the potential for protein-based vaccines to provide direct protection against MenB disease in immunised children, further research is required to understand the breadth and duration of this protection. A more detailed understanding of the impact of immunisation with these vaccines on nasopharyngeal carriage of the meningococcus is also required, to inform both their potential to induce herd immunity and to preferentially select for carriage of strains not susceptible to vaccine-induced antibodies. Although a full understanding of the potential impact of these vaccines will only be possible with this additional information, the availability of new tools to prevent the devastating effect of invasive MenB disease is a significant breakthrough in the fight against childhood sepsis and meningitis.